The influence of spawning habitat restoration on juvenile brown trout ( Salmo trutta) density - Palm, Daniel; Brännäs, Eva; Lepori, Fabio; Nilsson, Kjell; Stridsman, Stefan (Canadian Journal of Fisheries and Aquatic Sciences, 2007)
Between 1992 and 2003, we assessed the density of age-0+ brown trout (Salmo trutta) in a channelized stream in northern Sweden, which was restored using two different schemes. One section of the stream was restored by the addition of boulders and reconstruction of gravel beds (boulder + gravel section), whereas another section was restored through addition of boulders only (boulder-only section). In addition, we compared the substrate size composition of gravel beds and the egg-to-fry survival between the two stream sections, and we related the density of age-0+ brown trout to the area of reconstructed gravel beds. After the restoration, the density of age-0+ brown trout increased significantly in the boulder + gravel section and was positively correlated with the area of reconstructed gravel beds. By contrast, the density of age-0+ brown trout did not change in the boulder-only treatment. Egg-to-fry survival was significantly higher in the boulder + gravel section compared with the boulder-only section, probably because of the higher content of sand and fines in the gravel beds of the latter treatment. This study shows that the density of age-0+ brown trout was limited by the availability and quality of spawning substrate rather than by the structural habitat complexity.